EDITORIAL - Vargas, J. V.C. (Revista de Engenharia Térmica, 2016)
The editorial of Engenharia Térmica of this issue continues the discussion on scientific research needs in vital areas in which thermal engineering has important participation. The main goal is to motivate the readers, within their specialties, to identify possible subjects for their future research. With the development of modern high resolution infrared cameras, the utilization of thermal imaging exams has gained new appeal in medical practice, although the method has been applied for the first time more than 60 years ago. The technique is noninvasive, there is no ionizing radiation emission, low cost, fast in image capturing and of easy application. However, there are some aspects such as method imprecision due to the individual metabolism and surrounding ambient temperature that interfere in precise results, making the method subjective. In Engineering it is a well established field, mainly for the detection of heat leaks in boilers, hot fluid pipes, and other equipment, in which high temperatures are observed, thus with high temperature gradients with respect to the ambient, that are much above measurements uncertainties, what allows for well conclusive analyses. On the other hand, surface temperatures on human skin are close to the ambient temperature, therefore the observed temperature gradients are small, what makes the analyses less conclusive. In sum, there is need for the development of structured methodologies for adequate selection of human body surface temperatures that are related to diverse diseases. Expected normality ranges could be established based on infrared imaging temperature measurements of volunteers without complaints. It is expected that measurements in patients previously diagnosed with traditional techniques (e.g., biopsy) fall out of such ranges. The main objective would be to concretely demonstrate that infrared imaging has potential for utilization as a noninvasive screening exam for people with complaints, what would indicate whether or not the individual should be submitted to a more complex exam. The mission of Engenharia Térmica is to document the scientific progress in areas related to thermal engineering (e.g., energy, oil and renewable fuels). We are confident that we will continue to receive articles’ submissions that contribute to the progress of science.